Gospel and wisdom Israel's wisdom literature in the Christian life - Goldsworthy, Graeme Lister, 1934- (Carlisle, UK Paternoster, 1987)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Wisdom literature -- criticism, interpretation, etc